1. Démontrer que pour tout nombre x:
(x+1)²-(x-1)²=4x

Merci d'avance.

1
(x+1)²-(x-1)²=4x

D’abord :
(x+1)²=x²+2*x*1+1²
(x+1)²=x²+2x+1

(x-1)²=x²-2*x*1+1²
(x-1)²=x²-2x+1²
Donc :
(x+1)²-(x-1)²=(x²+2x+1) – (x²-2x+1) ici il y a un – devant la parenthèse donc on change de signe la parenthèse :
x²+2x+1 – x²+2x-1=4x

Réponses

2014-10-24T17:09:52+02:00
(x+1)²-(x-1)²=4x

D’abord :
(x+1)²=x²+2*x*1+1²
(x+1)²=x²+2x+1

(x-1)²=x²-2*x*1+1²
(x-1)²=x²-2x+1²
Donc :
(x+1)²-(x-1)²=(x²+2x+1) – (x²-2x+1) ici il y a un – devant la parenthèse donc on change de signe la parenthèse :
x²+2x+1 – x²+2x-1=4x